'This is my life style, Arabic and English': students' attitudes to (trans)languaging in a bilingual university context. Issue 1 (3rd April 2018) - Palfreyman, David M.; Al-Bataineh, Afaf
ABSTRACT: Translanguaging is defined by Canagarajah as 'the ability of multilingual speakers to shuttle between languages, treating the diverse languages that form their repertoire as an integrated system'. University students in our own working context have grown up in a multilingual society and study courses in both Arabic (their first language) and English (the main language of instruction). They encounter new concepts and perspectives in both languages; and when they graduate, the intention is that they will be academically and professionally prepared to use both languages in their future career. However, it is not clear how they 'make sense of their bilingual worlds' or whether they feel able to 'shuttle between languages' in a way appropriate to their future working context. The study described here focuses on two students interacting around course-related content with a peer, with a simulated workplace audience and with a research interviewer. In this paper we focus on the participants' awareness of and attitudes towards Arabic, English and translanguaging both while engaged in the tasks and in reflection afterwards, revealing contrasting and sometimes contradictory attitudes to the deployment of their communicative repertoire.